Relation of disease activity with quality of life and sleep quality in knee osteoarthritis - Volkan Şah (Van Tıp Dergisi, 2021)
INTRODUCTION: The aim of this study was to assess the relation of disease activity with quality of life and sleep quality in knee osteoarthritis. METHODS: The study was performed on patients with knee osteoarthritis (n=100; 28 males, 72 females; mean age 58.09 years; range 23 to 85 years). Kellgren-Lawrence (KL) classification system, Visual Analog Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), World Health Organization Quality of Life (WHOQOL-BREF), and Pittsburgh Sleep Quality Index (PSQI) were used to evaluate radiological grading, pain, physical function (disease activity), quality of life, and sleep quality, respectively. RESULTS: There were significant positive correlations among KL, VAS, WOMAC, and PSQI scores, while significant negative correlations were found between WHOQOL-BREF profiles and KL, VAS, WOMAC, and PSQI scores (all p< 0.01). DISCUSSION AND CONCLUSION: Our results suggest that higher disease activity is related to lower quality of life and poorer sleep quality in knee osteoarthritis.